The Moderating Effects Of Environmental Awareness And Environmental Motivation On The Relationship Between Reward-Based Gamification And Pro-Environmental Behaviour: A Case Of Alipay’S Ant Forest - Huang, Miao (2024)
In order to cope with the environmental issues caused by rapid economic development, an environmental game called ant forest, developed by alipay, is used to advocate green awareness in china. The game mechanism of ant forest allows users to transform rewards into real trees. This study applied the stimulus-organism-response (s-o-r) theory as the theoretical foundation, analysed the direct relationships between gamified reward, perceived persuasiveness and pro-environmental behaviour (peb), and analysed the effect of environmental awareness and motivation as moderating variables. The study uses the explanatory sequential mixed methods to achieve the study objectives. In the first phase, 621 ant forest users participated in the survey through online questionnaires and this resulted in quantitative analysis results. In the second phase, the researcher selected 12 participants from the first phase to interview them face-to-face. The survey results show that reward-based gamification can be used as a very effective stimulating method to promote users’ peb. The stimulus work primarily through ant forest’s perceived persuasiveness on users. The more important finding of this study is that it proved the moderating effect of environmental awareness on the relationship between perceived persuasiveness and peb, while environmental motivation does not show the moderating effect.